2011
DOI: 10.1016/j.virol.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Potato spindle tuber viroid-specific small RNAs is accompanied by specific changes in gene expression in two tomato cultivars

Abstract: To better understand the biogenesis of viroid-specific small RNAs and their possible role in disease induction, we have examined the accumulation of these small RNAs in potato spindle tuber viroid (PSTVd)-infected tomato plants. Large-scale sequence analysis of viroid-specific small RNAs revealed active production from the upper portion of the pathogenicity and central domains, two regions previously thought to be underrepresented. Profiles of small RNA populations derived from PSTVd antigenomic RNA were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 66 publications
6
77
0
1
Order By: Relevance
“…2, Upper, small RNAs 9 and 10 in the small RNA assembly) and progressively enriched by PFOR. Therefore, PFOR was expected to identify viroids because current models suggest that viroid siRNAs are processed either from double-stranded head-to-tail repeats synthesized as replicative intermediates from the rolling-circle viroid replication or from the structural elements of the circular viroid RNA (3,(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, Upper, small RNAs 9 and 10 in the small RNA assembly) and progressively enriched by PFOR. Therefore, PFOR was expected to identify viroids because current models suggest that viroid siRNAs are processed either from double-stranded head-to-tail repeats synthesized as replicative intermediates from the rolling-circle viroid replication or from the structural elements of the circular viroid RNA (3,(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that infection of plants with viroids triggers abundant production of viroid-derived 21-, 22-, and 24-nt classes of small RNAs (sRNAs) in approximately equal plus and minus strand ratios, which are likely products of DCL4, DCL2, and DCL3, respectively (16)(17)(18)(19)(20)(21)(22)(23). We found that these viroid sRNAs overlapped in sequence and covered the entire length of viroid RNAs with high densities.…”
mentioning
confidence: 79%
“…4B and C). [84][85][86]88,89 In none of these analyses was an even distribution of vsRNA over the viroid genome observed, which would be expected if the vsRNA were derived of a putative complete viroid double-strand (see above). Instead, vsRNA appear to cluster as hotspots corresponding to certain regions of the viroid, which, however, cannot clearly be correlated with certain types of secondary structural elements.…”
Section: Causes Of Viroid Symptomsmentioning
confidence: 94%
“…Similar to endogenous small RNA in plants, 82 they feature sizes of 21 to 24 nucleotides in length. These small RNA have been found for PSTVd, 53,78,[83][84][85][86][87][88] ASBVd, 80 CEVd, 89 HSVd, [90][91][92] PLMVd, 93,94 and Grapevine yellow speckle viroid 1 (GYSVd1). 91 Small RNA molecules thus are a common feature of both viroid families, Pospiviroidae and Avsunviroidae.…”
Section: Viroid Infectionmentioning
confidence: 98%
See 1 more Smart Citation